Papal Bulls and Converso Brokers: New Christian Agents at the Service of the Catholic Monarchy in the Roman Curia (1550– 1650) - Díaz Rodríguez, Antonio J. (2016)
The minority who were of Iberian Jewish origin constituted a notable presence in sixteenth-century Rome. Part of that minority was also involved in the circuits formed around the issue of apostolic letters and the parallel phenomenon of alienation and commodification of ecclesiastical benefices.All these factors made some conversos from Portugal and Spain excellent candidates for managing these curial affairs, either as brokers hired by individuals or as servants of the Catholic monarchy. This paper focuses on the latter.